2021
DOI: 10.1248/cpb.c21-00169
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine Protects Glioblastoma Cells against Glutamate Toxicity by Suppressing Oxidative/Endoplasmic Reticulum Stress

Abstract: Thiamine (vitamin B1), which is synthesized only in bacteria, fungi and plants and which humans should take with diet, participates in basic biochemical and physiological processes in a versatile way and its deficiency is associated with neurological problems accompanied by cognitive dysfunctions. The rat glioblastoma (C6) model was used, which was exposed to a limited environment and toxicity with glutamate. The cells were stressed by exposure to glutamate in the presence and absence of thiamine. The differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
1
9
0
1
Order By: Relevance
“…Ergul et al. identified that thiamine protected glioblastoma cells against glutamate toxicity by inhibiting ATF4-associated endoplasmic reticulum stress ( 49 ). Recently, a TRAIL-inducing compound ONC201/TIC10 was found to promote apoptosis and integrated stress response in multiple tumors by activating ATF4 ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ergul et al. identified that thiamine protected glioblastoma cells against glutamate toxicity by inhibiting ATF4-associated endoplasmic reticulum stress ( 49 ). Recently, a TRAIL-inducing compound ONC201/TIC10 was found to promote apoptosis and integrated stress response in multiple tumors by activating ATF4 ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since glutamate receptor subtypes (ionotropic and metabotropic) are expressed in C6 glioblastoma cells, these cells can be a beneficial model for investigating excitotoxicity [ 18 ]. Moreover, C6 glial cells provide physical and metabolic support to the survival of neurons, such as insulation and communication of neurons and transportation of nutrients and waste; hence, glial cell damage may play role in the neurodegeneration process.…”
Section: Discussionmentioning
confidence: 99%
“…São necessárias para sustentar a glicose e aminoácidos no organismo. Além disso a tiamina é um fator benéfico para cada indivíduo, considerada micronutriente essencial no organismo humano (Ergül & Taşkıran, 2021).…”
Section: Vitaminas Do Complexo Bunclassified